2015
DOI: 10.1128/aem.04058-14
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of d -Glucose from Pentoses by Metabolically Engineered Escherichia coli

Abstract: T he pentose phosphate (PP) pathway interconverts phosphosugars having 3 to 7 carbon atoms principally by the action of the reversible enzymes transketolase and transaldolase. During the consumption of hexoses such as D-glucose or D-fructose, entry of carbon into this pathway provides many microorganisms, including Escherichia coli, the means to generate the reduced cofactor NADPH and to synthesize specific building-block compounds derived from intermediates of this pathway (e.g., phenylalanine, histidine, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 50 publications
2
5
0
Order By: Relevance
“…Previous studies with agp knockouts coding glucose‐1‐phosphatase demonstrated that glucose‐6P, and not glucose‐1P, is the primary phosphorylated source of glucose in E. coli ptsG manZ glk pfkA zwf , a result which is consistent with glucose‐6P formation being favored in the equilibrium with glucose‐1P mediated by phosphoglucomutase .…”
Section: Introductionsupporting
confidence: 54%
See 4 more Smart Citations
“…Previous studies with agp knockouts coding glucose‐1‐phosphatase demonstrated that glucose‐6P, and not glucose‐1P, is the primary phosphorylated source of glucose in E. coli ptsG manZ glk pfkA zwf , a result which is consistent with glucose‐6P formation being favored in the equilibrium with glucose‐1P mediated by phosphoglucomutase .…”
Section: Introductionsupporting
confidence: 54%
“…Escherichia coli MEC143 has deletions in the genes which provide for glucose conversion to glucose‐6P ( ptsG , manZ , glk ), and in key genes involved in the metabolism of glucose‐6P and fructose‐6P ( zwf , pfkA ). MEC143 has been established to accumulate glucose by the dephosphorylation of glucose‐6P when grown on either xylose or l ‐arabinose . Mass glucose yields of 0.260 g glucose/g xylose and 0.316 g glucose/g l ‐arabinose were observed in shake flask studies using 5 g/L of either pentose (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations